2D Material Optoelectronics for Information Functional Device Applications: Status and Challenges. Issue 11 (8th April 2020) - Tan, Teng; Jiang, Xiantao; Wang, Cong; Yao, Baicheng; Zhang, Han
Abstract: Graphene and the following derivative 2D materials have been demonstrated to exhibit rich distinct optoelectronic properties, such as broadband optical response, strong and tunable light–mater interactions, and fast relaxations in the flexible nanoscale. Combining with optical platforms like fibers, waveguides, grating, and resonators, these materials has spurred a variety of active and passive applications recently. Herein, the optical and electrical properties of graphene, transition metal dichalcogenides, black phosphorus, MXene, and their derivative van der Waals heterostructures are comprehensively reviewed, followed by the design and fabrication of these 2D material‐based optical structures in implementation. Next, distinct devices, ranging from lasers to light emitters, frequency convertors, modulators, detectors, plasmonic generators, and sensors, are introduced. Finally, the state‐of‐art investigation progress of 2D material‐based optoelectronics offers a promising way to realize new conceptual and high‐performance applications for information science and nanotechnology. The outlook on the development trends and important research directions are also put forward. Abstract : Herein, the latest research progress and development trends of optoelectronic information devices based on 2D materials are summarized. This work gives a comprehensive review of this field, covering the optoelectronic properties of 2D materials, preparation and composite processes, as well as specific applications and prospects, aiming to provide readers a communication platform with references.